1989
DOI: 10.1080/00288330.1989.9516354
|View full text |Cite
|
Sign up to set email alerts
|

Swimming performances of some native freshwater fishes

Abstract: Observations were made of the response to water velocity for upstream migrating juveniles of 5 diadromous native fishes (Anguilla auslralis, Galaxiasmaculatus,Galaxiasfasciatus,Retropinna relropinna, Gobiomorphus colidianus). Swimming performance within a hydraulic flume was measured and observations made of the behavioural adaptions of some species to swim through high water velocities. Timed swimming at known water velocities allowed estimation of critical velocities for fish passage. For juvenile fishes (30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(47 citation statements)
references
References 8 publications
2
45
0
Order By: Relevance
“…Water velocities at the WCS slots were too low (<0.2 m/s) to limit the migration of most nekton and only exceeded the swimming capabilities of larvae and small (e.g., <3 cm) juveniles (e.g., Mitchell 1989;Luckenbach and Orth 1992;Faria et al 2009). Individuals migrating out of managed marshes have been reported to be larger than those leaving unmanaged marshes (e.g., penaeid shrimps; Knudsen et al 1989Knudsen et al , 1996, ostensibly due to emigration impedance (resulting in long retention times), reduced predation, or decreased competition in managed marshes (Hoese and Konikoff 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Water velocities at the WCS slots were too low (<0.2 m/s) to limit the migration of most nekton and only exceeded the swimming capabilities of larvae and small (e.g., <3 cm) juveniles (e.g., Mitchell 1989;Luckenbach and Orth 1992;Faria et al 2009). Individuals migrating out of managed marshes have been reported to be larger than those leaving unmanaged marshes (e.g., penaeid shrimps; Knudsen et al 1989Knudsen et al , 1996, ostensibly due to emigration impedance (resulting in long retention times), reduced predation, or decreased competition in managed marshes (Hoese and Konikoff 1995).…”
Section: Discussionmentioning
confidence: 99%
“…34 (MTL) elvers of the American eel (Davidson 1949). Although Mitchell (1989) Although data from successful negotiations of fishways by juvenile eels in Australia does provide some indication of their swimming ability, this data alone is insufficient. A study by Kowarsky & Ross (1981) found that small numbers of 47-60 mm A. reinhardtii glass eels and elvers were able to ascend particular cells of the Fitzroy River fishway (a vertical slot fishway) where velocities did not exceed 69-90 cm s -'.…”
Section: Introductionmentioning
confidence: 99%
“…The relative effort expended by swimming animals was categorised into four groups based on both the observed inflection points within the data (corresponding to distinct changes in the level of effort), and arbitrary categories modified from Beamish (1978) and Mitchell (1989). These different levels of effort were designated as sustained, steady prolonged, rapid prolonged, and burst.…”
Section: Quantifying Swimming Effortmentioning
confidence: 99%
See 2 more Smart Citations